2018
DOI: 10.4274/tjod.73600
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset neonatal infection in pregnancies with prelabor rupture of membranes in Kosovo: A major challenge

Abstract: Objective:Prelabor rupture of membranes (PROM) is a common event in obstetrics that has a major impact in pregnancy outcome. This condition is linked to a number of pregnancy and birth complications with early-onset neonatal infection (EONI) being one of the major threats. This study was undertaken to determine the rate of neonatal infection in newborn infants with a maternal history of PROM and to evaluate the association of risk factors with neonatal infection following PROM.Materials and Methods:A cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…evident in 5% of cases. 8 In this study from total of 72 subjects with preterm premature of membrane (PPROM), there were 22 (31%) early-onset neonatal sepsis (EONS)-suspected newborns while 50 (69%) newborns were not EONS-suspected. These results were higher than in other studies.…”
Section: Discussionmentioning
confidence: 89%
“…evident in 5% of cases. 8 In this study from total of 72 subjects with preterm premature of membrane (PPROM), there were 22 (31%) early-onset neonatal sepsis (EONS)-suspected newborns while 50 (69%) newborns were not EONS-suspected. These results were higher than in other studies.…”
Section: Discussionmentioning
confidence: 89%
“…In the research results of Gutbir et al it is stated that an Apgar score with a low score is at risk of experiencing neonatal sepsis with a relative risk of 1.28, in line with the results of research from 9 literatures discussing Apgar scores with a low score can be 3 times greater risk to suffer from neonatal sepsis (p value<0.05, 95% CI: 1.3-7-7, OR: 3.2). 1,[9][10][11][12][13][14][15][16] Assessment of the Apgar score can be done at the same time as the examination of sex, gender is one of the risk factors for neonatal sepsis. The gender at risk for infection is higher in the male sex, this is in accordance with the results of the study of Murthy, et al that male infants are 1.3 times higher risk of infection (p value=0.03, 95% CI: 1.02-1.68, OR: 1.3) compared to female infants, this is in line with the results of 5 literature studies which state that male sex is at risk 1.31 (p value=0.003, 95% CI: 1.22-1.41, OR: 1.31) had a higher risk of infection and even death than women.…”
Section: Resultsmentioning
confidence: 99%
“…15 The 1st minute Apgar score with a value less than 7 has a 1.5 times greater risk of infection (p value=0.01, 95% CI: 5.7-0.99). 16 There is a difference in risk values between the Apgar score for values less than 7 seen at the 1 st minute and seen from the 5 th minute, this is because asphyxia causes immunological disorders and requires resuscitation intervention after birth, this tends to give time for bacteria to have the opportunity to explore self in newborns. 12 Table 3 shows that there is a significant relationship between gender and the occurrence of morbidity in the male sex with a relative risk of 1.20 (p value=0.001, 95% CI: 1.02-1.40, RR: 1.40), this study is in line with 7 other studies which state that there is a significant relationship between the occurrence of infection and gender but the results of the study by Ndombo et al showed that gender was not associated with the occurrence of neonatal sepsis (p value=0.4621).…”
Section: Resultsmentioning
confidence: 99%
“…Complications of PROM for the fetus and newborn consist of prematurity, fetal distress, cord compression, deformation and altered pulmonary development leading to pulmonary hypoplasia and pulmonary hypertension, necrotizing enterocolitis (NEC) and neurologic disorder (5) . Infectious morbidities in mother, fetus and newborn have been related to both PROM and prolonged rupture of membranes (6) .…”
Section: Introductionmentioning
confidence: 99%